Extraction and characterization of bioactive compounds from hibiscus flower via microwave-assisted hydrodistillation (MAHD) - Rassem, Hesham H. A.; Nour, A. H.; R. M., Yunus (Centre of Lipids Engineering and Applied Research (CLEAR), UTM, 2017)
In this study, the influence of several experimental parameters on the Microwave-assisted Hydrodistillation (MAHD) extraction of Hibiscus flower was investigated: extraction time, solvent polarity, sample amount, solvent volume and sample particle size. It was concluded that the most influential variables were extraction time and solvent polarity. The optimized procedure employed 35 g of ground flowers, 280 mL of methanol and 120 min of extraction. The extracts were fractionated using preparative silica columns (30 m * 0.25 mm i.d., film thickness 0.25 mm). Oven temperature was programmed to 60 oC for 10 min, and then increased at 20 oC/min to 230 oC and held at 250 oC for 10 min. The carrier gas, helium, was adjusted to a linear velocity of 30 cm/s and the resulting fractions were analyzed by Gas Chromatography-mass Spectroscopy (GC-MS). Some saturated hydrocarbons and fatty acid methyl esters were identified in theHIbiscus flowers extracts. Thirty-seven compounds were identified, representing 99.9.% of the oil. The main components were Ethanimidic acid, ethyl ester (31.43%), Propanal, 2,3-dihydroxy (12.58%) and 4H-Pyran-4-one, 2,3-dihydro-3,5-di hydroxy-6-methyl (10.69%).